Financial Sustainability of Immunization Programs in sub-Saharan Africa - (:unkn) unknown (My University, 2013)
The introduction of new vaccines with much higher prices than traditional vaccines results in increas-ing budgetary pressure on immunization programs in GAVI-eligible countries, increasing the need toensure their financial sustainability. In this context, the third EPIVAC (Epidemiology and Vaccinology)technical conference was held from February 16 to 18, 2012 at the Regional Institute of Public Healthin Ouidah, Benin. Managers of ministries of health and finance from 11 West African countries (GAVIeligible countries), as well as former EPIVAC students and European experts, shared their knowledge andbest practices on immunization financing at district and country level.The conference concluded by stressing five major priorities for the financial sustainability of nationalimmunization programs (NIPs) in GAVI-eligible countries.
Keywords: African Research